(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2013)
The natural landmark "Valley of Kurgans" is situated within coastal solonchak plain formed near the Yagorlitsky Bay of the Black Sea. In this area a rare habitat in Ukraine, which in Europe is called «saltmarsch» is represented. It is an unique place in terms of valuable halophytic vegetation and also of the huge number of kurgans located in this area. For the conservation of such diversity the creation of regional landscape park is proposed. Тhе annotated list of the vascular plants «Valley of Kurgans» includes 333 species of vascular plants belonging to 194 genera and 45 families, 2 classis, 2 divisions. Among them, 16 species are included to the different Red List.